2022
DOI: 10.3390/ijerph191912407
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Publications on the Omicron Variant from 2020 to 2022 in the Scopus Database Using R and VOSviewer

Abstract: Human respiratory infections caused by coronaviruses can range from mild to deadly. Although there are numerous studies on coronavirus disease 2019 (COVID-19), few have been published on its Omicron variant. In order to remedy this deficiency, this study undertook a bibliometric analysis of the publishing patterns of studies on the Omicron variant and identified hotspots. Automated transportation, environmental protection, improved healthcare, innovation in banking, and smart homes are just a few areas where m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 57 publications
(56 reference statements)
0
18
0
Order By: Relevance
“…The thematic map analysis of keywords allows for the organization of keyword groupings according to their density and centrality into a single circle for mapping as a two-dimensional image ( Ejaz et al, 2022 ). From the Keyword plus, it was identified that motor topics including “growth performance”, “supplementation”, “ascorbic acid research”, and “meat quality”, have been well-researched with respect to heat stress in poultry ( Mahmoud et al, 2004 ; Abidin and Khatoon, 2013 ; Kumar et al, 2021 ; Piray and Foroutanifar, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The thematic map analysis of keywords allows for the organization of keyword groupings according to their density and centrality into a single circle for mapping as a two-dimensional image ( Ejaz et al, 2022 ). From the Keyword plus, it was identified that motor topics including “growth performance”, “supplementation”, “ascorbic acid research”, and “meat quality”, have been well-researched with respect to heat stress in poultry ( Mahmoud et al, 2004 ; Abidin and Khatoon, 2013 ; Kumar et al, 2021 ; Piray and Foroutanifar, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…By typing Biblioshiny() into the R terminal, the Biblioshiny application was started. A number of tools made available by Bibliometrix enable investigators to conduct comprehensive bibliometric analyses [ 18 , 19 , 20 , 21 ]. It allows the display of multiple results in tables and graphs, which is a feature difficult to find in other software.…”
Section: Methodsmentioning
confidence: 99%
“…Due to a rising in publications related to Omicron, some bibliographic cluster analyses were proposed to better summarise literature results ( Ejaz et al, 2022 ; Liu et al, 2023 ) and give a comprehensive prospect of all the connected potential impacts. The results show that publications focused on specific environments and public health issues.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these bibliometric analyses allowed us to provide a clearer understanding of the available information about this SARS-CoV-2 variant and focalise attention on the eventual knowledge gaps. It is interesting to highlight that the literature's focus was changed from 2020 to 2022: the keywords such as anxiety, resiliency, mental health, and lockdown of 2020 were replaced by behaviour, social distancing, risk perception, immunization, and telemedicine in 2021 ( Ejaz et al, 2022 ). According to the scientific search engines (SCOPUS and Web of Science), just limited studies dealing with the “spread” (or “diffusion”) of the emerging new variant “Omicron” have been published (specifically, 481 documents can be found in SCOPUS on September 26, 2022), in comparison to more than 18,200 papers devoted to discussing the diffusion of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%